Pemanfaatan Data Satelit Terhadap Prediksi Curah Hujan - Dicky Muhamad Fadli (Institut Teknologi Garut, 2022)
With the introduction of a new emission scenario, namely the Representative Concentration Pathways (RCP) which is used for the latest climate models so that it can model future climates. Climate predictions can be used to predict rainfall which can be used for various hydrological analyses. The RCP data used is RCP 85 which is calibrated with local rainfall. From the calibration results obtained statistical parameters close to the rain station. By using the gamma distribution, the number of days and the amount of rain can be calculated. From the analysis results, it is predicted that in 2029 there will be 2126 mm/year of rainfall with 121 rainy days with a configuration of 6 months of wet classification, 2 months of normal classification and 4 months of dry classification.